Tzanck Smear in Dermatologic Practice. Issue 1 (January 2022) - Yang, Ronald A.; Nodine, Sarah; Anderson, Jaclyn B.; Laughter, Melissa R.; Zangara, Tessa; Dinkel, Rebecca; Dunnick, Cory A.
Abstract : ABSTRACT: The Tzanck smear was introduced in the 1950s and has been used for the diagnosis of erosive, vesiculobullous, tumoral, and granulomatous diseases. The Tzanck smear is rapid, easy to perform, and relatively inexpensive. Results from this diagnostic test can be obtained at the bedside, often within several minutes. Tzanck smears have high diagnostic reliability for erosive/vesiculobullous and granulomatous lesions. For some lesions, the sensitivity of Tzanck smears can exceed 80% up to 90% depending on the expertise of the user. However, for more challenging diagnoses, Tzanck smear should be used in conjunction with more advanced techniques to ensure an accurate clinical diagnosis. This article reviews the background, indications, construct, and applications of the Tzanck smear to highlight this commonly used diagnostic tool in dermatology.